Sensory evaluation of flavoring agent addition in soy-based beverage - Pratiwi, Riyona Desvy; Rosyidi, Viddy Agustian; Zanjabilla, Sabighoh; Dewi, Kartika Sari; Novandra, Rio; Desvina, Della; Herawati, Heny (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2022)
Soy-based beverages offer numerous health benefits, but the presence of lipoxygenases causes an unpleasant off-flavor sensation that hinders acceptability. The addition of a suitable flavoring agent has been shown to enhance the acceptability of soy-based beverages. This study aimed to investigate preferences towards two flavored variants of soy-based beverages: original chocolate made from cocoa powder and vanilla made from vanilla essence. Before comparing the sensory parameters, which included appearance, taste, odor, texture, and overall assessment, the ratio of basic components such as soy and cow milk powder, sugar, and maltodextrin was studied. Fifty-seven untrained panelists evaluated the three flavored variants of soy-based beverages. The chocolate-flavored soy-based beverage received a significantly higher score in taste, odor, texture, and overall assessment (α = 0.05). Hence, adding cocoa powder as a flavoring agent in soy-based beverages effectively improved the sensory attributes.